Clinical significance of genetic alterations in endoscopically obtained pancreatic cancer specimens. (16th January 2021) - Takano, Shinichi; Fukasawa, Mitsuharu; Shindo, Hiroko; Takahashi, Ei; Hirose, Sumio; Fukasawa, Yoshimitsu; Kawakami, Satoshi; Hayakawa, Hiroshi; Kuratomi, Natsuhiko; Kadokura, Makoto; Maekawa, Shinya; Sato, Tadashi; et al.
Abstract: Although comprehensive gene analyses of pancreatic cancer provide new knowledge on molecular mechanisms, the usefulness and possibility of the analyses in routinely available clinical samples remain unclear. We assessed the possibility and utility of target sequencing of endoscopically obtained pancreatic cancer samples. Fifty‐eight pancreatic cancer patients who underwent EUS‐FNA or endoscopic biopsy were enrolled. The extracted DNA quantity was assessed and used for next‐generation sequencing (NGS) of 50 cancer‐related genes from which gene mutations, copy number alterations, and microsatellite instability (MSI) were extracted via secondary analysis. A median of 19.2 ng (3.8–228) of DNA was extracted from formalin‐fixed paraffin‐embedded samples. Gene alterations were detected in 55 of 58 samples (94.8%), including all samples with a DNA concentration below the detection limit ( n  = 11). Four frequently altered genes were KRAS (83%), TP53 (66%), SMAD4 (26%), and PTEN (17%), and molecular targetable genes were detected in 13 cases (22.4%). Five samples (8.6%) had many mutations and suspected MSI with impaired mismatch repair genes. A Cox regression analysis revealed that metastasis ( p  < 0.005, hazard ratio [HR] 10.1), serum CEA >5 ng/ml ( p  = 0.01, HR 2.86), ≤10 detected hotspot mutations ( p  = 0.03, HR 9.86), and intact Ras signaling ( p  < 0.005, HR 5.57) were associated with a poor pancreatic cancer prognosis. We performed small, targeted sequencing of pancreatic cancer using available samples from real clinical practice and determined the relationship between gene alterations and prognosis to help determine treatment choices. Abstract : We performed next‐generation sequencing of endoscopically obtained formalin‐fixed paraffin‐embedded tissue samples from actual clinical samples of patients with pancreatic cancer to evaluate gene alterations and potential prognostic indicators. This targeted sequencing of cancer‐related genes was informative for predicting prognosis and selecting therapy.